Defence‐related gene expression of Hevea brasiliensis clones in response to the white rot pathogen, Rigidoporus microporus. Issue 4 (14th January 2016) - Oghenekaro, A. O.; Omorusi, V. I.; Asiegbu, F. O.
Summary: Gene expression levels of pathogenesis‐related proteins (PR1, PR3, PR5, PR8 and PR9), cell wall modification genes (PAL and expansin), signal transduction genes (ACC oxidase, AOC, MAPK) and a Myb transcription factor were compared in two Hevea brasiliensis budded clones (RRIM612 and PR107) 5 weeks after wounding and artificial inoculation with the white rot fungus, Rigidoporus microporus . PR3 class I chitinase was upregulated in RRIM612 in response to the pathogen when compared with the wounded control. PR9 class IV peroxidase was highly upregulated in PR107. PR1 and PR8 were expressed more in wounded than in inoculated clones. Genes involved in ethylene and jasmonic acid signalling pathways and phenylalanine ammonia‐lyase (PAL) were upregulated almost equally in both clones. The Myb transcription factor was upregulated in RRIM612, while MAPK was upregulated in PR107 when compared to the wounded control. The predicted expansin‐like protein was upregulated 40‐fold in RRIM612 when compared to the wounded control. The results demonstrate the variability in defence responses in different clones and provide the first set of defence genes expression profiles in the host–pathogen interaction of the white rot disease of rubber trees.